Dialectic of Fear: Centre-Liberal Media Discourse on Gender, LGBTQIA+ and Abortion in Contemporary Poland - Krzyżaniak, Aleksandra (Literatura Ludowa. Journal of Folklore and Popular Culture, 2022)
References to fear are often associated with narratives created by right-wing parties and media, especially while talking about issues such as gender, LGBTQIA+ or abortion. However, similar practices can be found in centre-liberal discourse, proving that the creation and reproduction of the dialectic of fear can apply to all agents, no matter their political affiliation. The article aims to challenge popular academic perceptions of the sources of fear by proposing a counterperspective that means to shift perception on agents of polarisation. Used examples focus on contemporary Polish mainstream centre-liberal newspapers which reproduce fear in their narrative, adding to both local and worldwide phenomena of political polarisation and radicalisation.